(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
In our republic next years resource efficient agricultural technologies wide scale attraction to do big attention is being directed. In this place Uzbekistan Republic for 2017-2021 intended actions strategy "Village farm work release to the branch intensive methods, first of all, water and resources thrifty modern agricultural technologies application is important from tasks one reached defined. This tasks account received without, soil productivity storage and improve and cotton from the crop high and good quality harvest in cultivation Fergana of the region grassland soils conditions new and promising cotton varieties of maintenance agrotechnics elements work exit according to scientific research take to go current is considered.